Effect of Thermal Stress on Thermoregulation, Hematological and Hormonal Characteristics of Caracu Beef Cattle - Abduch, Natalya G.; Pires, Bianca V.; Souza, Luana L. [UNESP]; Vicentini, Rogerio R.; Zadra, Lenira El Faro; Fragomeni, Breno O.; Silva, Rafael M. O.; Baldi, Fernando [UNESP]; Paz, Claudia C. P.; Stafuzza, Nedenia B. (MDPI, 2022)
This study evaluated the influence of environmental temperature on thermoregulation, hormonal, and hematological characteristics in Caracu cattle. Blood samples, hair length, coat and muzzle colors, rectal (RT), and surface temperatures were collected from 48 males and 43 females before (morning) and after sun exposure for eight hours (afternoon). Infrared thermography (IRT) was used to identify superficial temperature that exhibits a high correlation with RT. Hematological parameters, hormone concentrations, RT, and the superficial temperature obtained by IRT that exhibited the highest correlation with RT were evaluated by variance analysis. Regarding IRT, the lower left side of the body (LS) showed the highest correlation with the RT. Interaction between period and sex was observed for LS, cortisol, and eosinophils. Cortisone, progesterone, and RT were influenced by period and sex. Neutrophils and segmented neutrophils were influenced by the period, which showed the highest concentrations after sun exposure. Platelets, leukocytes, lymphocytes, and monocytes were influenced by sex. Heat stress changes several physiological characteristics where males and females exhibited differences in their responses to heat stress. Furthermore, most characteristics evaluated remained within the regular values observed for taurine Creole breeds, showing that Caracu is adapted to tropical climates.
Keywords: adaptability; Bos taurus; hemogram; infrared thermography; thermotolerance